Effect of Different Ablation Settings on Acute Complications Using the Novel Irrigated Multipolar Radiofrequency Ablation Catheter (nMARQ). (1st September 2015) - DENEKE, THOMAS; MÜLLER, PATRICK; HALBFAß, PHILIPP; SZÖLLÖSI, ATILLA; ROOS, MARKUS; KRUG, JOACHIM; FOCHLER, FRANZISKA; SCHADE, ANJA; SCHMITT, RAINER; CHRISTOPOULOS, GEORGIOS; MÜGGE, ANDREAS; NENTWICH, KARIN
Effects of Different Energy Settings in nMARQ Ablation Background Single‐shot ablation devices for pulmonary vein isolation (PVI) in patients with symptomatic atrial fibrillation (AF) have been increasingly used in clinical practice. Objective A novel mapping‐system integrated irrigated multipolar circular ablation catheter (nMARQ) has been introduced for PVI but data on larger patient cohorts on acute safety and efficacy are lacking. Methods A total of 145 consecutive patients undergoing AF ablation treated with the nMARQ underwent endoscopic evaluation of esophageal thermal damage (EDEL) and brain MRI for detection of silent cerebral events (SCE). During the course of our experience different modifications of the ablation strategy, including energy delivery at the left atrial posterior wall, were evaluated. Results Effective PVI was achieved in 99% of all PVs during a mean procedure‐duration of 115 (±36) minutes and ablation‐duration of 18 (±8) minutes. Acute major complications occurred in 3 patients (2.1%) and asymptomatic complications like SCE in 26% and EDEL in 21%. There was a significant reduction in EDEL when not using a thermal esophageal probe (0% vs. 28%, P < 0.0001). Ablation under oral anticoagulation led to lower SCE incidences compared to interrupted anticoagulation regimen (15% vs. 31%, P = 0.7). Out of 65 patients with completed 12‐month follow‐up, 43 (66%) were in stable sinus rhythm. Conclusions PVI using the nMARQ is safe and effective in patients with symptomatic AF. Not using an esophageal temperature probe during ablation has relevantly reduced the incidence of EDEL. Ablations under continued oral anticoagulation have reduced incidence of SCE. Further studies on long‐term efficacy are needed.